2017
DOI: 10.1038/s41598-017-08699-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CXCR4 on T-cell subsets and Plasma IL-17 Concentrations in Patients with Aplastic Anaemia

Abstract: Acquired aplastic anaemia (AA) is caused by T-cells migrating to and attacking bone marrow (BM) in response to chemokines (e.g., CXCR4). We investigated CXCR4 expressions on circulating T-cell subsets, plasma IL-17A concentrations, and their correlations with AA manifestations. We enrolled 71 patients with acquired AA (36 severe AA cases [SAA] and 35 non-severe AA cases [NSAA]) and 42 healthy volunteers. We used flow cytometry and ELISA to measure circulating CD4+ and CD8+ T-cells, their CXCR4 expressions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The former is a classic T-helper 1 cytokine involved in the autoimmune attack against bone marrow precursors typical of aplastic anemia (3) and reported elevated also in AIHA. Likewise, IL-17, a cytokine known to amplify the proinflammatory and autoimmune response, has been reported elevated in the same settings (17)(18)(19). In our study, PNH positive AIHA showed a Th1 profile more similar to hemolytic PNH than to "classic" (PNH negative) AIHA, suggesting that these small clones might mitigate Th1 response.…”
Section: Discussionsupporting
confidence: 62%
“…The former is a classic T-helper 1 cytokine involved in the autoimmune attack against bone marrow precursors typical of aplastic anemia (3) and reported elevated also in AIHA. Likewise, IL-17, a cytokine known to amplify the proinflammatory and autoimmune response, has been reported elevated in the same settings (17)(18)(19). In our study, PNH positive AIHA showed a Th1 profile more similar to hemolytic PNH than to "classic" (PNH negative) AIHA, suggesting that these small clones might mitigate Th1 response.…”
Section: Discussionsupporting
confidence: 62%
“…The CXCL12‐CXCR4 axis is not only important for homeostatic regulation of BM CD8 + T cells, but has also been implicated in the migration of pathogenic T cells to the BM. In aplastic anemia (AA), a disease characterized by T‐cell mediated destruction of the BM, CXCR4 is highly expressed on BM‐infiltrating CD4 + and CD8 + T cells in both mouse models and patients . In fact, symptoms of AA can be attenuated with pharmacological agents that block CXCR4 expression .…”
Section: Discussionmentioning
confidence: 99%
“…We further found differential expression of inflammatory pathway‐related genes, such as CXCR4 , on tumor‐infiltrating mast cells. CXCR4 is a chemokine receptor for CXCL12 that is expressed by inflammatory cells including T cells, macrophages, and mast cells, and has been shown to play a role in mast cell recruitment [25,32,33]. The CXCL12–CXCR4 pathway in mast cells has been causally implicated in several cancers, including UV‐induced skin cancer, glioblastoma, and prostate cancer [34–36].…”
Section: Discussionmentioning
confidence: 99%